About Multiple Prolongations of Latin Cubes [Articol] - Sokhatsky, Fedir; Moroz, Daria (My University, 2024)
We propose an algorithm of prolongation of a Latin cube with k new elements (k ≥ 1).
Keywords: Latin cube; prolongation of Latin cube; twodimensionaltransversal; one-dimensional transversal; ternaryquasigroup; prolongation of ternary quasigroup; multiple prolongation of Latin cube